The effect of competence on job satisfaction and its impact on employee performance at the culture and tourism office of east Belitung Regency - Andhika Mochamad Siddiq; Ridlwan Muttaqin; Fanji Wijaya (Institute of Computer Science (IOCS), 2023)
Using the use of work satisfaction as a mediator, this study seeks to compare the direct and indirect effects of competency characteristics on employee performancebecause to improve employee performance the steps taken must be effective and efficient with strong evidence. According to Usman (2012), competence is defined as anything that both qualitatively and quantitatively represents a person's qualities or talents. Many researches have shown that competence has an impact on both employee performance and job satisfaction. Employee performance is influenced by job satisfaction as well, and it is considered that job satisfaction may be able to mediate the impact of competence on employee performance. There are 70 employees in total, and path analysis techniques are being used to determine which path, considering both direct and indirect affects, is the most effective. The study's findings indicate that every variable falls within the